Lipopolysaccharide‐induced sickness behavior is not altered in male Fmr1‐deficient mice - Danielle Santana‐Coelho; Samantha L. Hodges; Saul I. Quintero; Paige D. Womble; D. Greg Sullens; David A. Narvaiz; Rebecca Herrera; Melanie J. Sekeres; Joaquin N. Lugo (Brain and Behavior, 2023)
Abstract Objectives Fragile X syndrome is the main monogenetic cause of intellectual disability and autism. Alterations in the immune system are commonly found in these developmental disorders. We and others have demonstrated that Fmr1 mutant mice present an altered response to immune stimuli. However, whether this altered immune response can influence the Fmr1 mutant behavioral outcomes in response to inflammation has not been fully investigated. Materials and methods In the current study, we examine the behavioral sickness response of male wildtype and knockout  mice to the innate immune stimulus lipopolysaccharide (LPS) (0.1 mg/kg) to determine if Fmr1 mutants have altered sickness behavior. We used an enzyme‐linked immunosorbent assay (ELISA) to measure changes in the cytokine interleukin‐6 (IL‐6) to determine that inflammation was induced in the mice. Sickness behavior was assessed in a wheel‐running paradigm, and a tail suspension test was used to assess the depressive‐like phenotype that follows sickness behavior in response to LPS. Results The ELISA using blood serum confirmed a significant increase in IL‐6 in mice that were treated with LPS. Treated Fmr1 mutants exhibited decreased distance traveled in the wheel running after LPS administration, similar to treated controls. Another cohort of animals treated with LPS were tested in the tail suspension test and exhibited no alterations in immobility time in response to LPS. Conclusion Together, our data suggest that Fmr1 mutant mice do not have altered sickness behavior in response to a low dose of LPS.